2021
DOI: 10.31893/jabb.21032
|View full text |Cite
|
Sign up to set email alerts
|

Influence of climatic conditions on tympanic temperature and milk production in grazing cows

Abstract: Vasconcelos et al 2020). Animal's body temperature is traditionally estimated through rectal and vaginal measurements; however, alternative methods like tympanic temperatures (TT) also constitute a reliable measure since some studies reported no statistical difference with rectal temperatures (Sellier et al 2014;Shu et al 2021) and high correlation with vaginal temperature (r = 0.77; Bergen and Kennedy, 2000). The differences associated with the anatomical sampling point and its response time were also validat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…Similarly, it has been observed that in Holstein cows exposed to stressful temperature and humidity indices > 78 (equivalent to an average of 33.8 °C and 36% of maximum ambient temperature and minimum relative humidity, respectively), milk components such as fat, protein, lactose, TS, and SNF were significantly reduced [ 31 ]. In lowland tropical conditions, it has been shown that climatic variables such as mean temperature and solar radiation increased the tympanic temperature of tropical dairy cows, reducing their performance with values above 38.9 °C [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, it has been observed that in Holstein cows exposed to stressful temperature and humidity indices > 78 (equivalent to an average of 33.8 °C and 36% of maximum ambient temperature and minimum relative humidity, respectively), milk components such as fat, protein, lactose, TS, and SNF were significantly reduced [ 31 ]. In lowland tropical conditions, it has been shown that climatic variables such as mean temperature and solar radiation increased the tympanic temperature of tropical dairy cows, reducing their performance with values above 38.9 °C [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…De acuerdo, a la ubicación de cada uno de los sistemas ganaderos se le asignó la estación meteorológica más cercana. La distancia entre las estaciones y los sistemas estudiados fue: Sistema uno (6.2 km), Sistema dos (5.4 km), Sistema tres (5.6 km) y Sistema cuatro (6.5 km) (24). Las variables analizadas fueron temperatura ambiental (°C), radiación solar (cal/cm 2 ), humedad relativa (%), velocidad del viento (m/s) y precipitación (mm).…”
Section: Recolección De Datosunclassified